Differential proteomic analysis of fetal and geriatric lumbar nucleus pulposus: immunoinflammation and age-related intervertebral disc degeneration - Chensheng Qiu; Xiaolin Wu; Jiang Bian; Xuexiao Ma; Guoqing Zhang; Zhu Guo; Yan Wang; Yandong Ci; Qizun Wang; Hongfei Xiang; Bohua Chen (BMC Musculoskeletal Disorders, 2020)
Abstract Background Intervertebral disc degeneration (IVDD) is a major cause of low back pain. Although the mechanism of degeneration remains unclear, aging has been recognized as a key risk factor for IVDD. Most studies seeking to identify IVDD-associated molecular alterations in the context of human age-related IVDD have focused only on a limited number of proteins. Differential proteomic analysis is an ideal method for comprehensively screening altered protein profiles and identifying the potential pathways related to pathological processes such as disc degeneration. Methods In this study, tandem mass tag (TMT) labeling was combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) for differential proteomic analysis of human fetal and geriatric lumbar disc nucleus pulposus (NP) tissue. Parallel reaction monitoring (PRM) and Western blotting (WB) techniques were used to identify target proteins. Bioinformatic analyses, including Gene Ontology (GO) annotation, domain annotation, pathway annotation, subcellular localization and functional enrichment analyses, were used to interpret the potential significance of the protein alterations in the mechanism of IVDD. Student’s t-tests and two-tailed Fisher’s exact tests were used for statistical analysis. Results Six hundred forty five proteins were significantly upregulated and 748 proteins were downregulated in the geriatric group compared with the fetal group. Twelve proteins were verified to have significant differences in abundance between geriatric and fetal NP tissue; most of these have not been previously identified as being associated with human IVDD. The potential significance of the differentially expressed proteins in age-related IVDD was analyzed from multiple perspectives, especially with regard to the association of the immunoinflammatory response with IVDD. Conclusions Differential proteomic analysis was used as a comprehensive strategy for elucidating the protein alterations associated with age-related IVDD. The findings of this study will aid in the screening of new biomarkers and molecular targets for the diagnosis and therapy of IVDD. The results may also significantly enhance our understanding of the pathophysiological process and mechanism of age-related IVDD.